2017
DOI: 10.1002/mbo3.511
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the oligopeptide permeases in multistep of Vibrio alginolyticus pathogenesis

Abstract: Vibrio alginolyticus has been associated with several diseases of cultivated marine animals, and has led to considerable economic losses. The oligopeptide permease (Opp) has been proven to play a variety of important roles in nutrition and virulence in several bacteria. In our previous research, the opp gene cluster was identified in Vibrio alginolyticus with transcriptome sequence, which also indicated that the Opp system might play roles in the regulation of adhesion. In this study, the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 49 publications
1
40
0
Order By: Relevance
“…A QuantStudio™ 6 Flex real‐time PCR system (ABI, USA) was used to carry out qRT–PCR with SYBR green I (Dongsheng, China) as instructed by the manufacturer (Liu, Huang, et al., ). The expression level of rpoS was assessed, with 16S RNA expression used for normalization ( n = 6).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A QuantStudio™ 6 Flex real‐time PCR system (ABI, USA) was used to carry out qRT–PCR with SYBR green I (Dongsheng, China) as instructed by the manufacturer (Liu, Huang, et al., ). The expression level of rpoS was assessed, with 16S RNA expression used for normalization ( n = 6).…”
Section: Methodsmentioning
confidence: 99%
“…Reverse transcription was carried out with A Reverse Aid Mu-MLV cDNA synthesis kit (TransGen Biotech, China) from 2.0 mg total RNA, as instructed by the manufacturer (Zhang, Huang, Zhao, & Hu, 2017). instructed by the manufacturer (Liu, Huang, et al, 2017). The expression level of rpoS was assessed, with 16S RNA expression used for normalization (n = 6).…”
Section: Total Rna Extraction and Reverse Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighty healthy E. coioides were randomly divided into four groups. Each fish was intraperitoneally injected with 100 μl of wild‐type or stable silenced strains of P. plecoglossicida (1 × 10 7 cfu/ml) at 18°C (Liu et al, ), while sterile PBS was chosen as a negative control. Infected fish were observed daily until 10 days post‐injection.…”
Section: Methodsmentioning
confidence: 99%
“…Manual curation of the genes associated with GATC motifs related to phenotypic changes showed that many of them were involved in (1) transcription regulation, (2) cell metabolism, (3) nutrient capture and transport into the cell, (4) excretion into the outer medium, (5) cell envelope structure (including peptidoglycan and lipopolysaccharide biosynthesis) and (6) biofilm formation, adherence or motility (Figure 5, gene functions panel and Supplementary Tables S5–S11). Many of those functional categories have been shown to be critical for pathogen virulence in other bacterial species, in particular for nutrient capture in the challenging host medium (Ren et al, 2018; Liu et al, 2017), for recognition of the host habitat via its nutrient signature (López-Garrido et al, 2015; Krypotou et al, 2019) and for biofilm formation, adherence and motility which have a key role in colonization and successful invasion of the host tissues (Turner et al, 2009; Luo et al, 2017). The numerous candidate genes involved in lipopolysaccharide biosynthesis also suggest that the O antigen, which can classically be involved both in cell recognition by phages and in bacterial virulence in its host (Chart et al, 1989; Li and Wang, 2012), could act as a major player of evolutionary trade-offs between bacterial virulence and resistance to phage infection.…”
Section: Figurementioning
confidence: 99%